(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
In today’s globalized world, the ability to communicate across cultures is essential, making foreign language education a crucial component of modern curricula. However, effective language teaching extends beyond just vocabulary and grammar; it must also consider the students’ diverse social backgrounds. Understanding the social context in which a student lives can significantly influence how they learn and use a new language. This article explores the importance of tailoring foreign language teaching to students’ social backgrounds and provides strategies for educators to better support diverse learners.